Analisis Phubbing pada Instagram terhadap Kualitas Interaksi Langsung dan Social Satisfaction di Universitas Boyolali - Revinta Santiara Siringoringo; Puspitasari, Ayu; Roso Prajoko (LPPM Stikosa - AWS, 2025)
This study aims to analyze the impact of Instagram usage on the social interactions of Universitas Boyolali students, highlighting the phenomenon of phubbing and its effects on the quality of face-to-face communication and social satisfaction levels. Phubbing refers to the behavior of ignoring direct interactions in favor of focusing on mobile phone usage, a phenomenon increasingly common among active social media users, especially Instagram users, within the student demographic. The research adopts John C. Creswell's descriptive qualitative approach and utilizes Miles and Huberman's data analysis techniques. In-depth interviews were conducted with several Universitas Boyolali students who regularly use social media, particularly the Instagram app. The findings reveal that excessive Instagram usage can disrupt the quality of direct social interactions. Most respondents acknowledged that their attention is often diverted by notifications and entertainment features on Instagram, leading to a decline in face-to-face communication quality. Furthermore, the phenomenon of phubbing has the potential to damage interpersonal relationships, with respondents emphasizing the importance of time management in Instagram usage. This study also highlights the importance of self-awareness in managing social media usage to maintain the quality of social relationships and direct communication. The findings contribute to understanding the impact of social media on student social interactions and offer insights for individuals and educational institutions to manage the negative effects of excessive social media use.